Opinia . pismo Ruchu Obrony Praw Człowieka i Obywatela, no. 11, 1978 - [Leszek Moczulski EIC] (Wydawnictwo Polskie, 1978)
Creation and circulation: Journal republished legally in 1990; Some numbers published in various versions, both single- and double-sided, also in 21 cm. format